A study of physiochemical parameter of dissolved oxygen (DO) and biochemical oxygen demand (BOD) generated from industrialization activities that impacted stream of Santubong river - Mior Izzuddin, Baharuddin (Universiti Malaysia Sarawak (UNIMAS), 2014)
Demak Laut Industrial Park is a rapidly growing industrial area located beside the Santubong River of Sarawak. This river is being used by the fishermen to catch fish and shrimp for their food and also their own economics. The increasing of rapid industrialization has exerted immense pressure on water quality by introducing a large variety of chemicals into the environment. This study was carried out to determine the water quality of Santubong River. Water samples were collected from three (3) different strategic locations of Santubong River. The physio-chemical characteristics of water, including temperature, pH, conductivity, dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), salinity, total dissolved solids (TDS), total suspended solids (TSS), turbidity, ammoniacal nitrogen (NH3-N) and oil and grease (O&G) were measured by in-situ water monitoring equipment and also a laboratories analysis to determine status in relation to the health of the river ecosystem. The total data points were used to establish relationships between the parameters and data were also subjected to statistical analysis and expressed as mean ± standard error of mean (SEM) at the level of significance of p<0.05. The mean value of the measured parameters was compared with National Water Quality Index Department of Environment Malaysia (DOE-WQI). Present level concentration of ammoniacal nitrogen, biochemical and chemical oxygen demand were under the categorization of Class I, II and III while total suspended solids were categorized in Class III. The impact of industrial activities may cause some environmental problem to the Sungai Santubong and adjacent areas and also the ecosystem in the rivers in the long terms. Therefore, some sort of the integrated river water management and good industrial practice should be implemented.